Nucleus accumbens response to rewards and testosterone levels are related to alcohol use in adolescents and young adults. (February 2016) - Braams, Barbara R.; Peper, Jiska S.; van der Heide, Dianne; Peters, Sabine; Crone, Eveline A.
Abstract: During adolescence there is a normative increase in risk-taking behavior, which is reflected in, for example, increases in alcohol consumption. Prior research has demonstrated a link between testosterone and alcohol consumption, and between testosterone and neural responses to rewards. Yet, no study to date tested how testosterone levels and neural responses to rewards relate to and predict individual differences in alcohol use. The current study aimed to investigate this by assessing alcohol use, testosterone levels and neural responses to rewards in adolescents (12–17 years old) and young adults (18–26 years old). Participants were measured twice with a two-year interval between testing sessions. Cross-sectional analysis showed that at the second time point higher neural activity to rewards, but not testosterone levels, explained significant variance above age in reported alcohol use. Predictive analyses showed that, higher testosterone level at the first time point, but not neural activity to rewards at the first time point, was predictive of more alcohol use at the second time point. These results suggest that neural responses to rewards are correlated with current alcohol consumption, and that testosterone level is predictive of future alcohol consumption. These results are interpreted in the context of trajectory models of adolescent development.